An analysis of corporate image, product image, user image and country image on muslim consumer puchase desicion towards halal food product: a case study in Johor Bahru / Fifi Miliza Zolkifle - Zolkifle, Fifi Miliza (2016)
In an era of increased competition, companies nowadays are bound to make substantial efforts to manage their brand image. Nevertheless, the news abounds with instances of firms finding themselves in the middle of an unforeseen, boycott-caused, marketing crisis stemming from a controversial event with which the firm has no explicit, direct relation. (Senet al., 2001). The purpose of this paper is to analyze the effect of brand image dimension on purchase decision. Corporate image, product image, user image and country image will be used to measure the factors that Influence community in Johor Bahru in purchasing decision. This research aims to examme the influence of Corporate Image, User Image, Product Image and Country Image Toward Purchase Decision in Johor Bahru. The type of this research is Explanatory Research. The research is conducted in Johor Bahru area only and 200 questionnaires were distributed randomly to the people who live there. The sampling technique used is simple random sampling and the research instruments were tested using the Frequency Analysis, Factor Analysis, Reliability Test, Pearson Correlation Coefficient and Regression Analysis. The multiple regression analysis result shows that Corporate Image, User Image, and Product Image have significant effect simultaneously and partially toward Purchase Decision. The dominant test shows that User Image is the most dominant variable influencing the Purchase Decision. The result of this research can be applied for Marketing Strategy. The company should retain the brand image in order to always have a positive image in the consumers' eyes that will influence their decision in purchasing decision.